Isolated cytochrome c oxidase deficiency as a cause of MELAS. Issue 2 (1st February 2008) - Rossmanith, W; Freilinger, M; Roka, J; Raffelsberger, T; Moser-Thier, K; Prayer, D; Bernert, G; Bittner, R E
Abstract : Background: MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes) is one of the more common mitochondrial encephalomyopathies. About 80% of MELAS cases are caused by transition 3243A→G in the mitochondrial tRNA Leu(UUR) gene ( MT-TL1 ). Other mutations in MT-TL1, other mitochondrial tRNA genes and mitochondrial-encoded subunits of respiratory complex I account for the remainder of cases. Objective: To characterise the molecular basis of a MELAS case without a mutation in any recognised MELAS target gene. Results and methods: Deletion of a single nucleotide (7630delT) within MT-CO2, the gene of subunit II of cytochrome c oxidase (COX), was identified by mitochondrial DNA (mtDNA) sequencing. The deletion-induced frameshift results in a stop codon close to the 5′ end of the reading frame. The lack of subunit II (COII) precludes the assembly of COX and leads to the degradation of unassembled subunits, even those not directly affected by the mutation. Despite mitochondrial proliferation and transcriptional upregulation of nuclear and mtDNA-encoded COX genes (including MT-CO2 ), a severe COX deficiency was found with all investigations of the muscle biopsy (histochemistry, biochemistry, immunoblotting). Conclusions: The 7630delT mutation in MT-CO2 leads to a lack of COII with subsequent misassembly and degradation of respiratory complex IV despite transcriptional upregulation of its subunits. The causal association of the resulting isolated COX deficiency with MELAS is at odds with current concepts of the biochemical deficits underlying this common mitochondrial disease, and indicates that the genetic and pathobiochemical heterogeneity of MELAS is greater than previously appreciated.